2009
DOI: 10.5194/bgd-6-9781-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Summer microplankton community structure across the Scotia Sea: implications for biological carbon export

Abstract: Abstract. During the austral summer of 2008, we carried out a high resolution survey of the microplankton communities along a south to north transect covering a range of environments across the Scotia Sea, Southern Ocean; high and low productivity, sea-ice to open water conditions, and over a number of oceanographic fronts and bathymetric features. Cluster analysis revealed five distinct communities that were geographically constrained by physical features of bathymetry and fronts. From south to north the comm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…We put forward the hypothesis that ikaite precipitation had occurred in the sea ice brines of the Weddell–Scotia Confluence during the preceding winter and the resultant DIC‐ and TA‐poor brines were released into the underlying water as the ice melted, transferring the inorganic carbon characteristics into the summer mixed layer. The absence of calcifying phytoplankton in this region (Korb et al, 2010) supports the proposed mechanism of the observed depletion in DIC and TA at the sea surface.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We put forward the hypothesis that ikaite precipitation had occurred in the sea ice brines of the Weddell–Scotia Confluence during the preceding winter and the resultant DIC‐ and TA‐poor brines were released into the underlying water as the ice melted, transferring the inorganic carbon characteristics into the summer mixed layer. The absence of calcifying phytoplankton in this region (Korb et al, 2010) supports the proposed mechanism of the observed depletion in DIC and TA at the sea surface.…”
Section: Discussionsupporting
confidence: 73%
“…Chlorophyll‐a concentrations sharply decreased to a minimum of 0.21 mg m −3 beneath the sea ice at station 1. For the MIZ (stations 1–6), the phytoplankton community was dominated by naked, heterotrophic dinoflagellates with diatoms accounting for between 21 and 46% of the total cell abundance (Korb et al, 2010). North of the South Orkney Islands to 59°S (stations 8–13) the community consisted of a mixture of dinoflagellates and cryptophytes, with less than 20% diatoms (Korb et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the AAZ west of South Georgia, diatoms also dominate phytoplankton biomass in late summer with a strong contribution of Pseudo‐nitzschia , T. antarctica , and E. antarctica var. antarctica (Korb and Whitehouse ; Korb et al ). We observed a strong contribution of the very large diatom Thalassiothrix antarctica together with Corethron spp.…”
Section: Discussionmentioning
confidence: 99%
“…As phytoplankton stocks (Boyce et al, 2010) and diatom production (Bopp et al, 2005) decline globally under climate change, carbon export to deeper layers via diatom blooms will be affected (Korb et al, 2010). Additionally, in the Southern Ocean, intense grazing on diatoms by krill efficiently transfers biomass to higher trophic levels (Smetacek et al, 2004).…”
Section: Introductionmentioning
confidence: 99%